Tennis Rehabilitation Training-Assisted Paclitaxel Nanoparticles in Treatment of Lung Tumor - Di Hu; YiMin Yang (Journal of Chemistry)
Paclitaxel nanoparticles are a compound with unique anticancer effects. Its mechanism of action is to prevent tumor rupture by stabilizing tumor proteins, while preventing cell division, leading to cell death, thereby inhibiting the spread of lung tumors. This article aims to study the treatment of lung tumors with paclitaxel nanoparticles assisted by tennis rehabilitation training. In this paper, paclitaxel nanoparticles were prepared by a solvent displacement method, and their particle size and morphology were measured. The TA2 series of experimental rats were selected to establish animal lung tumor models, and they were randomly divided into 5 groups: local injection of saline, porphyrin, and low-, medium-, and high-dose paclitaxel nanoparticles for treatment. The experimental results in this paper show that the average particle size of the paclitaxel nanoparticles prepared in the experiment is about 153,54 nm. Each treatment group inhibited tumor development to varying degrees. Among them, the inhibitory volume rate of paclitaxel nanoparticles in the middle- and high-dose groups was significantly higher than that in the paclitaxel treatment group, indicating that paclitaxel nanoparticles can release drugs slowly.